Fabrication and characterization of porous CaSiO3 ceramics. Issue 3 (15th February 2019) - Hu, Yue; Xiao, Zhen; Wang, Huanping; Ye, Can; Wu, Yuqian; Xu, Shiqing
Abstract: Porous CaSiO3 ceramics were prepared via a solid-state reaction method using CaCO3 and SiO2 as raw materials and active carbon as a pore-forming agent. The results indicated that porous CaSiO3 ceramics could be obtained under a low sintering temperature of 1320 °C. The addition of active carbon significantly affected the volume density, microstructure, pore size distribution and mechanical strength of porous CaSiO3 ceramics. With the increase of active carbon content, the volume density decreased, meanwhile the pore size and porosity increased gradually. Besides, the three-point bending tests demonstrated that the mechanical strength was decreased with increasing active carbon content. However, all the porous ceramics still exhibited high mechanical strength. These results implied that the increase of active carbon content not only enlarged the pore size and enhanced the porosity, but also kept a remarkable mechanical strength of porous CaSiO3 ceramics. Therefore, these rationally designed CaSiO3 porous ceramics will be a highly potential material in various applications due to its high mechanical strength, low sintering temperature and narrow pore size distribution.